1989
DOI: 10.1159/000288157
|View full text |Cite
|
Sign up to set email alerts
|

Use of Imipramine in Children with Intractable Asthma and Psychiatric Disorders: A Warning

Abstract: Imipramine is an established treatment for anxiety in adults. Some evidence also exists that it may be beneficial in children. Because of the frequent co-occurrence of anxiety and affective symptomatology in asthmatic children, a pilot study was undertaken to obtain clinical observations on the effects of imipramine on symptoms of asthma as well as those of separation anxiety and depression in children suffering from intractable asthma. The pilot trial was terminated because of medical complications after 6 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Finally, side effects have been reported when asthma medications are utilized in conjunction with psychiatric medications. Kanner et al (1989) have raised this concern when a pilot trial of psychiatric medication with a group of asthmatics was terminated due to medical complications. Koenig (1988) reviewed asthma treatment with inhaled corticosteroids and, despite the case of a 5-year-old girl who became acutely psychotic with high doses of corticosteroids, concluded that these medications were safe.…”
Section: Medication Effectsmentioning
confidence: 99%
“…Finally, side effects have been reported when asthma medications are utilized in conjunction with psychiatric medications. Kanner et al (1989) have raised this concern when a pilot trial of psychiatric medication with a group of asthmatics was terminated due to medical complications. Koenig (1988) reviewed asthma treatment with inhaled corticosteroids and, despite the case of a 5-year-old girl who became acutely psychotic with high doses of corticosteroids, concluded that these medications were safe.…”
Section: Medication Effectsmentioning
confidence: 99%